PENERAPAN METODE RESITASI DALAM MENULIS TEKS ANEKDOT SISWA KELAS X DPIB SMK NEGERI 1 BATIPUH - Laila Fitri (FKIP UMSB, 2018)
This research is a research writing anecdotal text in class X DPIB SMK Negeri 1 Batipuh. In addition, the students' lack of knowledge about writing anecdotal texts and the limited knowledge of students about the structure, linguistic characteristics, and rules of anecdotal texts. Students find it difficult to put their ideas into the anecdotal texts they make. This is known based on information from Indonesian language teachers who taught in class X DIPB at SMK Negeri 1 Batipuh. This type of research consists of quantitative with a quasi-experimental method (quasi-experimental). The research design used was One-Group Pretest-Posttest Design with a purposive sample technique. The sample in this study were 29 people taken from the total population of 342. The instruments used were performance tests. Data collection techniques are carried out by the following steps; (1) Conduct the initial test (pretest) (2) Give a score, (3) Carry out learning to write paragraph descriptions by applying the recitation method, (4) Carry out the final test (posttest) students write paragraph descriptions, (5) Worksheet results of student posstest collected and assessed based on predetermined indicators. Data are analyzed by procedure: (1) reading and correcting the results of student writing according to the indicators, (2) giving and recording scores, (3) changing the score to value, (4) classifying, (5) determining the calculated average value, ( 6) describe the test results, (7) hypothesis testing. The results showed that the application of the recitation method had a significant effect on the ability to write paragraphs description of students kelals X DPIB SMK Negeri 1 Batipuh. This can be seen from the value of the average ability to write paragraph descriptions after the application of the recitation method (784.00) compared to the average ability to write paragraphs of descriptions of students before applying the recitation method (71.50). Besides that, it can be seen from the results of the t-test which proves that t count> t table (4.92> 1.70).